Exploring the Boundaries of Microbial Habitability in Soil. Issue 6 (23rd June 2021) - Dragone, Nicholas B.; Diaz, Melisa A.; Hogg, Ian D.; Lyons, W. Berry; Jackson, W. Andrew; Wall, Diana H.; Adams, Byron J.; Fierer, Noah
Abstract: Microbes are widely assumed to be capable of colonizing even the most challenging terrestrial surface environments on Earth given enough time. We would not expect to find surface soils uninhabited by microbes as soils typically harbor diverse microbial communities and viable microbes have been detected in soils exposed to even the most inhospitable conditions. However, if uninhabited soils do exist, we might expect to find them in Antarctica. We analyzed 204 ice‐free soils collected from across a remote valley in the Transantarctic Mountains (84–85°S, 174–177°W) and were able to identify a potential limit of microbial habitability. While most of the soils we tested contained diverse microbial communities, with fungi being particularly ubiquitous, microbes could not be detected in many of the driest, higher elevation soils—results that were confirmed using cultivation‐dependent, cultivation‐independent, and metabolic assays. While we cannot confirm that this subset of soils is completely sterile and devoid of microbial life, our results suggest that microbial life is severely restricted in the coldest, driest, and saltiest Antarctic soils. Constant exposure to these conditions for thousands of years has limited microbial communities so that their presence and activity is below detectable limits using a variety of standard methods. Such soils are unlikely to be unique to the studied region with this work supporting previous hypotheses that microbial habitability is constrained by near‐continuous exposure to cold, dry, and salty conditions, establishing the environmental conditions that limit microbial life in terrestrial surface soils. Plain Language Summary: Microorganisms are the most ubiquitous forms of life on Earth and can be found in even the most challenging environments. As a result, it is often assumed that microbes have come to inhabit every terrestrial surface on Earth. Previous work has hinted that soil environments, without any detectable microorganisms or microbial activity, might exist in Antarctica. To explore this potential limit of habitability, we used a range of approaches, including culturing, DNA sequencing, and metabolic assays to explore patterns of microbial communities in Antarctic surface soils. By testing >200 soils collected across the Shackleton Glacier region, we sought to confirm whether microbial life in Antarctic surface soils is effectively undetectable under certain conditions. While we detected diverse microbial communities in many soils, we could not detect microbes in ∼20% of the collected samples. Our results suggest that microbial habitability is limited by the unique combination of cold, dry, salty conditions experienced at inland, higher elevation sites throughout the Transantarctic Mountain. Additionally, the prevalence of fungi at many of the most challenging sites suggests that fungi may be better adapted to some of the most challenging soil environments on Earth than bacteria and archaea. Key Points: Microbial life in Antarctic surface soils can be severely restricted by constant exposure to cold, dry, salty conditions Certain fungi may be better adapted than bacteria or archaea to some of the most challenging soil environments on Earth